ANALISIS INFERTILITAS PADA PASANGAN USIA SUBUR DI DUSUN V DESA SUMBER MELATI DISKI TAHUN 2025 - Manulang, Nisha Fortuna; Asfriyati,; Sri Rahayu Sanusi,; Panjaitan, Arifa Masyitah (Journal of Innovation Research and Knowledge, 2025)
Infertility, defined as the inability to conceive after 12 months of unprotected intercourse, often leads to psychological distress and social stigma. This study analyzed the causes, impacts, and coping strategies of infertility among reproductive-age couples in Dusun V, Sumber Melati Diski Village through a qualitative case study involving in-depth interviews with three couples selected by snowball and purposive sampling. Findings indicate that infertility was associated with smoking, alcohol consumption, drug use, obesity, unhealthy dietary, and occupational exposure to welding fumes. The impacts included psychological consequences such as sadness, anxiety, low self-esteem, loneliness, and anger, as well as social consequences in the form of negative stigma. Coping strategies identified were engaging in activities, self-isolation, denial of infertility examinations, reliance on traditional medicine, seeking informational support, adoption, maintaining a positive outlook, and recognizing the value of the partner’s presence. Strengthening partner support, adopting healthy lifestyles, and seeking professional healthcare such as midwives are recommended for effective management.